QUALITY OF LIFE AND UPPER LIMB FUNCTION OF CHILDREN WITH NEONATAL BRACHIAL PLEXUS PALSY - Daiane Lazzeri de Medeiros; Natália Borges Agostinho; Luis Mochizuki; Anamaria Siriani de Oliveira (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To compare the upper limb function and quality of life between children with neonatal brachial plexus palsy and controls with unaffected brachial plexus (typical children). Methods: Twenty-four children with neonatal brachial plexus palsy and 24 typical ones were evaluated, both groups with 10±3 years of age. The upper limb function was assessed by the Modified Mallet Scale and the Active Movement Scale, whereas quality of life was analyzed by the Pediatric Outcome Data Collection Instrument and the Child Health Questionnaire. Mann-Whitney U tests investigated the differences between groups in such scales. Results: Children with neonatal brachial plexus palsy presented lower limb function compared to typical children in both scales. These children also presented lower scores for most of the Pediatric Outcome Data Collection Instrument domains, except for comfort/pain. In addition, they had lower scores in the following domains of the Child Health Questionnaire: physical functioning, pain, behavior, mental health, overall health perception, emotional impact on parents, and psychosocial summarized score. Conclusions: Neonatal brachial plexus palsy has a negative influence on upper limb function and quality of life, mainly considering overall health, basic mobility, physical and psychosocial functions, happiness, pain, behavior, mental health, upper limb function, and emotional impact on their parents.